2012
DOI: 10.1007/s10549-012-2271-6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell markers are associated with adverse biomarker profiles and molecular subtypes of breast cancer

Abstract: Cumulative evidence has demonstrated the presence of cancer stem cells (CSC) in breast cancer and its putative role in cancer progression. Nonetheless, the clinical significance of CSC in breast cancer remains elusive. The underlying reasons could be due to the heterogeneity of breast cancer subtypes as well as different markers used to define breast CSC. In this study, three widely used markers (aldehyde dehydrogenase (ALDH)1+ and CD24-CD44+) were used to define two populations of CSC in a large cohort of bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 33 publications
4
55
0
Order By: Relevance
“…The association with hormone unresponsiveness has been reported previously (Ginestier et al , 2007; Nalwoga et al , 2010; Zhou et al , 2010; Tsang et al , 2012). Although ER- and PR-negative tumours tend to be more aggressive, ALDH1 expression did not correlate with recurrence or death, and failed to predict survival, in our study.…”
Section: Discussionsupporting
confidence: 68%
“…The association with hormone unresponsiveness has been reported previously (Ginestier et al , 2007; Nalwoga et al , 2010; Zhou et al , 2010; Tsang et al , 2012). Although ER- and PR-negative tumours tend to be more aggressive, ALDH1 expression did not correlate with recurrence or death, and failed to predict survival, in our study.…”
Section: Discussionsupporting
confidence: 68%
“…They found that the combination of CD44 + /CD24 - and ALDEFLUOR activity enabled them to isolate tumor cells able to form tumors with fewer numbers compared to the cells sorted by ALDEFLUOR activity alone; however, they did not investigate the clinical implications of this combination 9 . Actually, recent studies have shown that a combined analysis of BCSC markers can robustly predict outcome, but it works only limited to a subset of breast cancer 48-50. The current study demonstrated that the combined BCSC phenotype with CD44 + /CD24 - and ALDH1A1 could be an independent predictor of PFS in TNBC.…”
Section: Discussionmentioning
confidence: 54%
“…Aggressive breast tumors have high MCSC content that promotes not only progression of the disease but also its recurrence and metastasis (49). As few as 500 stem cell/cancer stem cells, that express aldehyde dehydrogenase-1 (ALDH1) in aggressive human breast tumors, have been found to initiate xenograft formation in nude mice (50).…”
Section: Discussionmentioning
confidence: 99%